Association between coexisting hypertension, dyslipidaemia and elevated C reactive protein with cardiovascular disease and mortality: a cross-sectional and longitudinal analysis in a representative cohort of older US adults - Thomas Leonidas Karadimas; Helen C S Meier (BMJ Public Health)
Objective Hypertension and dyslipidaemia are established risk factors for cardiovascular disease (CVD) but they are often insufficient on their own to predict CVD. Inflammation also contributes to CVD, but research on the co-occurrence of inflammation, hypertension and dyslipidaemia and CVD risk is limited. Knowledge of inflammatory status in addition to other risk factors is vital for clinicians to correctly evaluate patients for CVD risk.Methods Prospective data from the Health and Retirement Study, a representative cohort of US adults over 50 years of age (n=7895), were used. The average participant age was 68.8 years, and 54.9% were female. 80.7% were non-Hispanic white, 10.1% were non-Hispanic black and 9.2% were Hispanic. Hypertension, dyslipidaemia and elevated C reactive protein (CRP) were used to create a CVD risk score: low (0–1 factors), medium (2 factors) or high (all 3 factors). Measurement and definition guidelines for these variables are thoroughly explained in the methods section. Weighted logistic regression models estimated the OR of (1) prevalent and incident CVD for medium and high-risk groups versus the low-risk group and (2) 4-year mortality adjusting for covariates.Results Cross-sectionally, high-risk participants (n=1706) had significantly higher odds of CVD prevalence compared with participants with low-risk (n=3107) (adjusted OR 1.54, 95% CI: (1.29 to 1.84)). Medium-risk (n=3082) participants had higher odds of CVD prevalence, though this did not reach significance. Prospectively, medium-risk and high-risk participants had significantly higher odds of 4-year CVD incidence (medium-risk adjusted OR 1.57, 95% CI (1.18 to 2.09); high-risk adjusted OR 1.67, 95% CI (1.19 to 2.36)) compared with those with low risk. Risk of 4-year mortality was higher in high-risk (OR 2.12, 95% CI (1.60 to 2.8)) participants versus low-risk, and non-significantly elevated in medium-risk participants.Conclusions Co-occurrence of hypertension, dyslipidaemia and elevated CRP was strongly associated with increased CVD prevalence, higher incident CVD and elevated 4-year mortality in older US adults, emphasising the importance of multifactor screening for CVD risk.